Thoracic discectomy by tubular retractor: Clinical case - Amit C Jhala; Shivam K Kiri; Sharvil Gajjar (Indian Spine Journal, 2020)
Thoracic disc herniation is a rare condition in spine surgery. Surgical treatment is indicated for myelopathy, intractable radiculopathy, or persistent axial back pain. Various open approaches (anterior, anterolateral, posterior, or posterolateral), for thoracic discectomy have been described. These approaches have morbidity and a lot of collateral muscle damage. Minimally invasive approaches have been developed to decrease the morbidity of the open approaches. Here we describe the case of central thoracic disc herniation, which was operated by a minimally invasive transforaminal approach with technical details.